Interaction among lignocellulosic biomass components in thermochemical processes - Ricciulli, Miriam O. [UNESP]; Arce, Gretta L.A.F. [UNESP]; Vieira, Eliana C. [UNESP]; Ávila, Ivonete [UNESP] (Elsevier, 2024)
This research aims to evaluate the thermal behavior of main components of biomass (hemicellulose, cellulose and lignin) in order to identify their synergistic effect in thermochemical processes. These components were isolated from sugarcane bagasse and straw using different chemical treatments and their chemical and physical-chemical characterizations were performed. Results showed that chemical treatments were adequate for cellulose and lignin isolation, although it was verified that more adequate methodologies must be sought for hemicellulose isolation. The thermogravimetric analysis of each sample and their mixtures in inert (N2) and oxidant (synthetic air) atmospheres allowed investigating the synergism among the components. It was observed that the synergistic effect was more pronounced in DTG curves in an oxidizing atmosphere. There was a weak interaction effect between cellulose and hemicellulose, but hemicellulose allowed reducing cellulose decomposition rate. Moreover, the mixture between hemicellulose and lignin showed a synergistic effect on lignin, which promoted an increase in hemicellulose decomposition rate, while hemicellulose anticipated the main event of lignin decomposition in an oxidizing atmosphere. It was found that lignin had a positive effect on cellulose decomposition in an oxidizing atmosphere, thus inhibiting its decomposition, while cellulose promoted an increase in lignin decomposition rate in its final event. Ultimately, results for the synergistic effect allowed detecting other components besides isolated elements in the biomass structure in smaller amounts, which nevertheless affect the behavior of its thermal decomposition.